Zonation of the active methane-cycling community in deep subsurface sediments of the Peru trench - Lever, Mark A.; Alperin, Marc J.; Hinrichs, Kai-Uwe; Teske, Andreas (Frontiers in Microbiology, 2023)
The production and anaerobic oxidation of methane (AOM) by microorganisms is widespread in organic-rich deep subseafloor sediments. Yet, the organisms that carry out these processes remain largely uncharacterized. Here we identify members of the methane-cycling microbial community in deep subsurface, hydrate-containing sediments of the Peru Trench by targeting functional genes of the alpha subunit of methyl coenzyme M reductase (mcrA). The mcrA profile reveals a distinct community zonation that partially matches the zonation of methane oxidizing and –producing activity inferred from sulfate and methane concentrations and carbon-isotopic compositions of methane and dissolved inorganic carbon (DIC). Sequences belonging to putatively methane-oxidizing ANME-1a-b occur from the zone of methane oxidation to several meters into the methanogenesis zone. A sister group of ANME-1a-b, referred to as ANME-1d, and members of putatively aceticlastic Methanothrix (formerly Methanosaeta) occur throughout the remaining methanogenesis zone. McrA sequences appear absent from sulfate-rich sediments that are devoid of methane. Analyses of 16S rRNA and mcrA-mRNA indicate that the methane-cycling community is alive throughout (rRNA to 230 mbsf) and active in at least parts of the sediment column (mRNA at 44 mbsf). Carbon-isotopic depletions of methane relative to DIC (-80 to -86‰) suggest mostly methane production by CO2 reduction but are seemingly at odds with the widespread detection of ANME-1 and members of the aceticlastic Methanothricacea family.